A decision support framework for economic evaluation of flexible strategies in pavement construction projects. Issue Volume 20:Issued 11(2019) (2nd November 2019) - Nezhadpour Esmaeeli, Asghar; Heravi, Gholamreza
ABSTRACT: A fuzzy real options methodology is utilised to help highway management organisations select the supreme alternative for project implementation. The uncertainties inherited from input factors, i.e. unit costs of construction work items, unit rates of user costs, annual traffic growth rate and annual discount rate, are addressed through fuzzy set theory, and the managerial flexibilities associated with initial construction, preventive maintenance and rehabilitation are modelled using real options (RO) theory. The framework presented for Pavement Alternative Selection by RO-based Decision Support system (PASRODS) is a software package that has been developed using a Microsoft Excel spreadsheet and Visual Basic for Applications and includes three main components: Database, Model and Reports . PASRODS analyses the project in a year-by-year staged backward dynamic programming solution. Application of PASRODS in a highway project case study in Iran demonstrates that taking the managerial flexibilities into account results in valuing the projects in a more rational and actual manner. On the other hand, considering different attitudes of the decision-maker may lead to changes in alternative ranking and help in selecting supreme one in terms of numerous aspects.